Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan Melalui Disiplin Kerja sebagai Variabel Intervening pada PT Tinaru - Shelbyna Revania Ramda Saragih; Selvi Yona Sari; Della Asmaria Putri (Universitas 45 Surabaya, 2025)
This research aims to analyze the effect of work motivation and job satisfaction on employee performance, with work discipline as an intervening variable at PT Tinaru. Work motivation and job satisfaction are key factors that determine the effectiveness and productivity of the workforce in an organization. This research employs a quantitative method with a survey approach, where data is collected through questionnaires distributed to employees of PT Tinaru. The data analysis technique used is multiple linear regression with a mediation test to examine the role of work discipline in the relationship between motivation and job satisfaction on employee performance. The results of the study indicate that work motivation and job satisfaction have a positive and significant effect on employee performance, both directly and through work discipline. Work discipline is proven to be an intervening variable that strengthens the relationship between work motivation and job satisfaction on employee performance. Therefore, the company is advised to enhance the factors that support work motivation and job satisfaction, as well as enforce work discipline to optimize employee productivity.